SYSTEMATIC LITERATURE REVIEW: INTEGRATION OF THE 'ADAT BASANDI SYARAK, SYARAK BASANDI KITABULLAH' (ABS-SBK) VALUES IN CHARACTER EDUCATION FOR ELEMENTARY SCHOOL STUDENTS - Fikra Nabhan; Yanti Fitria; Adrias; Fitrawati (Review of International Journal Education and School Leadership, 2025)
Effective character education in elementary schools must be rooted in local wisdom to ensure moral, cultural, and intellectual balance. The Minangkabau philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK) serves as a moral compass that unites religious and cultural dimensions in shaping students’ character. This study aims to synthesize the implementation, assessment, and main challenges of integrating ABS-SBK values into character education in elementary schools across West Sumatra. Using the Systematic Literature Review (SLR) method, data were systematically collected, analyzed, and synthesized from recent academic studies (2018–2025). Findings show that ABS-SBK integration occurs through curriculum contextualization in Islamic Religious Education (PAI), Science and Social Studies (IPAS), Language, and Arts. These subjects infuse values such as Raso Pareso, Baso Basi, and Adat Salingka Nagari to foster empathy, respect, environmental care, and social responsibility. Character assessment employs holistic methods such as portfolios, attitude rubrics, and project-based evaluations aligned with the Kurikulum Merdeka.  However, several critical challenges remain: erosion of values due to modernization and globalization, digital gaps that reduce real social interaction, inconsistent teacher training, and limited documentation of local learning materials. The study concludes that effective ABS-SBK integration requires strategic mitigation through teacher professional development, digital ethics education, curriculum innovation, and strengthened collaboration among schools, customary institutions, and religious bodies. This integration ensures that character education not only transmits knowledge but also nurtures the moral and cultural identity of the Minangkabau generation.